Roles And Responsibilities Of Notary Deed In Limited Liability Company (PT) In Order To Improve The Economy Of Indonesia Especially In Blora - Christian Bagoes Prasetyo; Aryani Witasari; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
The purpose of this study was to: 1) Knowing and To study Role in Making of Notary Deed of Limited Liability Company in order to boost the economy in Indonesia. 2) Knowing and To study Roles and Responsibilities of the Notary in order to boost the economy in Indonesia 3) Know and To study barriers of Notaries in Deed Limited Liability Company in order to boost the economy in Indonesia. The method used sociological juridical research specification employed is normative, data retrieval methods used primary data and secondary data, and then analyzed with descriptive analytical method.Based on the results of data analysis summarized that: 1) The role of the Notary of the government in economic development in Indonesia give legal certainty and legal protection in the field of engagement and agreement 2) the presence of a notary becomes the spirit of the country's economic and social life and economic growth of Indonesian society. 3) barriers of notaries are facing is the technical suppose that the shareholders can not show passbooks are used as evidence of the capital and system of AHU Online / Legal Administration System (SABH) are always changing and error system.Keywords: Notary Role; Responsibilities Notary Deed of Limited Liability Company; Economy of Indonesia; Blora.